Leaving no one behind: just energy transition of fossil fuel-producing countries - Volkan Ş. Ediger (Frontiers in Political Science)
The dual challenges of mitigating climate change and safeguarding our planet, alongside eradicating inequality and poverty to ensure prosperity for all humanity, represent the defining issues of the Anthropocene. Addressing these interconnected global crises requires inclusive, equitable, and fair actions, leaving no one behind. A just and equitable energy transition from fossil fuels to renewables is thus indispensable. To date, efforts have focused mainly on reducing fossil fuel consumption, particularly in fossil fuel-importing nations, often neglecting the unique circumstances of fossil fuel-exporting countries. This study hypothesis “achieving energy transition goals necessitates the comprehensive recognition, integration, and addressing of the specific needs and challenges faced by fossil fuel-exporting nations, ensuring their full and equitable participation in the transition process.” Through a critical analysis of the rights and responsibilities of fossil fuel-exporting countries within the energy law framework, the study concludes that a successful phase-out of fossil fuels will remain unattainable unless mechanisms are established to safeguard these nations’ economic and social welfare. Moreover, the incentives and support to reduce fossil fuel consumption must be extended to producing and transit countries to ensure a truly inclusive and sustainable global transition.